Determinants of Household Welfare among Seaweed Farming Communities: The Roles of Production, Cultivation Area, Prices, and Market Access - Irna, Rizky Agusriyanti; Pratiwi, Sulistya Rini; Kartini; Nainggolan, Yohanna Thresia; Rahmatika, Maula Fadhilata; Rahmawati, Meylin (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
This study examines the effects of seaweed production, cultivation area, selling prices, and market access on household welfare in seaweed farming communities. Seaweed is a strategic commodity in coastal economies, yet the welfare of farming households often remains vulnerable to production uncertainty, price volatility, and unequal access to markets. Using a quantitative research design, this study draws on survey data from 110 respondents to analyze the extent to which farm performance and market-related factors shape household welfare. The analytical framework includes descriptive statistics, a household welfare index, instrument reliability testing, and multiple linear regression. The findings indicate that selling price is the strongest predictor of household welfare, followed by production level, market access, and cultivation area. The model explains a substantial proportion of the variation in welfare, suggesting that improvements in farmer well-being depend not only on output expansion but also on stronger market integration and more stable marketing conditions. These results highlight the importance of price stabilization, improved access to market information, stronger farmer institutions, and better post-harvest and logistics systems. The study provides practical insight for designing rural development policies aimed at improving the resilience and welfare of coastal farming households.